The Effectiveness of Cupping Therapy with Slow Deep Breathing on Anxiety and Sleep Quality in Breast Cancer and Cervical Cancer Patients - Pipin Nurhayati; Sri Nur Hartiningsih; Yeni Isnaeni (Indonesian Journal of Global Health Research, 2026)
Breast cancer and cervical cancer are among the leading causes of death in women worldwide. Breast cancer and cervical cancer can cause psychological disorders in women who experience them, including anxiety and sleep disorders or poor quality sleep. Therefore, it is necessary to deal with anxiety and poor quality sleep in women with breast cancer and cervical cancer. One of the efforts that can be done is to provide cupping therapy and slow deep breathing. The purpose of this study was to determine the effect of cupping therapy and slow deep breathing on anxiety and sleep quality in patients with breast and cervical cancer. The design of this study is pre-experiment, one group pretest-posttest. The sampling technique used is consecutive sampling with inclusion and exclusion criteria, with a total of 15 respondents. This study used a HARS questionnaire with a validity value of 0.589, reliability of 0.793, and PSQI questionnaire with a validity value of 0.73, reliability of 0.83. Data analysis was performed using paired T-Tests. The results of this study showed that the anxiety score before treatment was 23.1 and the post-treatment score was 10.53, while the sleep quality score before treatment was 10.8 and the post-treatment score was 3.533 and the P-value was 0.000. In conclusion, cupping therapy and slow deep breathing have the effect of reducing anxiety and improving sleep quality in patients with breast and cervical cancer.